2022
DOI: 10.1097/md.0000000000029875
|View full text |Cite
|
Sign up to set email alerts
|

Aortic calcification is associated with coronary artery calcification and is a potential surrogate marker for ischemic heart disease risk: A cross-sectional study

Abstract: Coronary artery calcification, an established marker of atherosclerotic plaque burden associated with increased risk of coronary artery disease, is routinely evaluated using electron beam computerized tomography or multidetector computed tomography (CT). However, aortic calcification, which is also a risk factor for adverse cardiac events, is not frequently assessed, despite being easily detected via standard chest radiography. We therefore sought to clarify the association between aortic calcification and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
2
0
0
Order By: Relevance
“…Recent studies have shown that aortic calcification is associated with coronary calcification 10 . The same finding was evident in our patient, as shown in Figures 2–4.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown that aortic calcification is associated with coronary calcification 10 . The same finding was evident in our patient, as shown in Figures 2–4.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, most cyclists had no aortic calcifications, and when present, the extension of this condition was low, with no impairment in aortic distensibility compared with nonathletes. Moreover, although aortic calcifications (including those in the ascending portion) have been previously associated with coronary calcifications (32), in the present cohort, former cyclists had similar CAC scores to controls, as reported in a previous study (17). In this regard, some evidence suggests that aortic calcifications are positively associated with cardiovascular risk, but this association disappears when adjusting for coronary calcifications (14).…”
Section: Discussionsupporting
confidence: 81%
“…There are not much data about the effect of alcohol on plaque progression either. A cross-sectional study showed that the levels of macrophage infiltration and lipid core volume among subjects who underwent femoral endarterectomy as well as coronary calcification measured by CT, were both inversely associated with alcohol consumption [40] . However, no studies providing visualization of coronary plaque volumes or longitudinal studies have been conducted [41] .…”
Section: Smoking and Alcoholmentioning
confidence: 99%